Isti'ab al-Qayyim al-Akhlaqiyyah min Khilal al-Af'al al-Taujihiyyah Asna'a Ta'lim al-'Arabiyyah - Lailatul Qomariyah; Akhmad Sauqi Ahya' (INAIFAS PRESS, 2022)
Character education is internalized in learning by focusing on character values so it helps students to understand and carry out social life. This study oriented to describe the internalization of character values through the teacher's directive speech in learning Arabic. This research used a qualitative case study approach. The data were collected by using the observation method and documenting it with a handycam and analyzing the context. The results of this study indicated the internalization of character valuesthrough teacher directive speech acts with six functions: 1) Asking by internalizing the value of curiosity; 2) Ordering to internalize the value of tolerance and independence; 3) Hoping by internalizing the value of hard work; 4) Inviting to internalize religious values; 5) Advising to internalize the value of appreciating achievement; and 6) Forbidding to internalize creative values. The results of this study contribute to Arabic teachers to communicate the internalization of character values in Arabic learning.